Target identification of HIV related ganoderic acids using molecular docking / Rahmad Akbar - Akbar, Rahmad (2011)
Four Ganoderic acids (á, B, C1 H) were studied using molecular docking approach. Both reverse molecular docking and molecular docking were combined to elucidate suitable target(s) for these Ganoderic acids. Outcomes from molecular docking were compared and correlated to experimental data. Compound with the best performance in both molecular docking and correlation analysis were further studied by looking at its molecular interaction with potential target. 1HVR (a type of HIV-1 protease) and Ganoderic acid B performed better in cluster analysis of molecular docking compared to other compounds. Similar ÄG trend to experimental data obtained from el-Mekkawy and co-workers (el-Mekkawy et al. 1998) were also observed. Molecular interaction study revealed Ganoderic acid B interactions with ILE50 and ILE50’ residues. These two residues has been identified as important residues and plays important roles in ligand-protein interaction in HIV-1protease (Lebon and Ledecq 2000). These interactions not only suggested HIV-1 protease in general is a suitable target for ganodericacid B, they also indicated a huge potential for HIV drug discovery based on this compound.